2012
DOI: 10.1111/j.1834-7819.2012.01690.x
|View full text |Cite
|
Sign up to set email alerts
|

Root caries and diabetes: risk assessing to improve oral and systemic health outcomes

Abstract: This report reviews the current understanding of the relationship between diabetes and root caries, and investigates the evidence for dental chairside testing of gingival crevicular blood (GCB) glucose levels to assess risk for type 2 diabetes mellitus. Diabetes is linked with the progression of periodontal disease and a greater number of exposed root surfaces at risk for root caries. The rapidly increasing prevalence of type 2 diabetes coupled with a general trend towards retention of teeth means that the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…However, it failed to prove these differences regarding type 2 diabetics. A higher risk of root caries is described for type 2 diabetics, which may be related to the increasing susceptibility to periodontal disease, but few studies aimed at evaluating this condition …”
Section: Resultsmentioning
confidence: 99%
“…However, it failed to prove these differences regarding type 2 diabetics. A higher risk of root caries is described for type 2 diabetics, which may be related to the increasing susceptibility to periodontal disease, but few studies aimed at evaluating this condition …”
Section: Resultsmentioning
confidence: 99%
“…In 2015, 3.4 million people in Saudi Arabia were diagnosed with diabetes . Besides several complications of diabetes such as neuropathy, retinopathy and nephropathy, it is also linked with the progression of periodontal disease and a greater number of exposed root surfaces at risk for root caries . The rapidly increasing prevalence of type 2 diabetes (T2D) coupled with a general trend towards retention of teeth means that the number of patients at increased risk for dental caries is increasing significantly .…”
Section: Introductionmentioning
confidence: 99%
“…Besides several complications of diabetes such as neuropathy, retinopathy and nephropathy, it is also linked with the progression of periodontal disease and a greater number of exposed root surfaces at risk for root caries . The rapidly increasing prevalence of type 2 diabetes (T2D) coupled with a general trend towards retention of teeth means that the number of patients at increased risk for dental caries is increasing significantly . Findings of the third National Health and Nutrition Examination Survey (NHANES‐III) demonstrated that dental caries occurs with substantial frequency and represents a burden of unmet treatment needs in older adults …”
Section: Introductionmentioning
confidence: 99%
“…As we know, impaired glucose regulation, hypertension, and dyslipidemia are main components of metabolic syndrome, which is a low-grade inflammatory condition associated with increased risk for diabetes and cardiovascular disease [30]. Studies have revealed that root caries is highly prevalent in patients with diabetes owing to periodontal attachment loss and gingival recession, compounded by reductions in salivary flow and elevated glucose level in their gingival crevicular fluid [3135]. A study has also revealed that hyperglycemia and insulin resistance were in strong relation to dental caries [30].…”
Section: Discussionmentioning
confidence: 99%